Anion stabilised hypercloso-hexaalane Al6H6 - Simon J. Bonyhady (Nature Portfolio, 2018)
While polyhedral boron hydride complexes have found application in a number of diverse fields, the isolation of stable aluminium analogues remains highly challenging. Here, Jones and colleagues demonstrate that reduction of an amidinato-aluminum(III) hydride complex with magnesium(I) dimers affords stable aluminium(I) hydride compounds.